Nursing management for 9 women with chickenpox at third trimester of pregnancy (9例妊娠晚期合并水痘孕妇护理体会) - LI Yan (李燕); LI Yuhua (李玉华); WANG Zhongying (王忠英) (Association of Integrative Nursing, 2022)
This paper reviewed the clinical data of 9 women with chickenpox at third trimester of pregnancy, and summarized related nursing measures. Pregnant women infected with Varicella should be arranged in the isolation ward, and appropriate cleaning and disinfection of contaminated items were implemented in the isolation ward. Based on the illness observation, comprehensive interventions on skin hygiene, hyperthermia, mental status and nutrition were carried out in the prenatal period. Key issues of postpartum care included prevention of postpartum complications, neonatal care, health education before discharge and home-based follow-up. A scientific and adequate nursing is effective to reduce the risk of postpartum complications and ensure the maternal and child safety. (本文回顾性分析9例妊娠晚期合并水痘孕妇的临床资料, 总结护理经验。产前应严格消毒隔离措施, 严密观察患者病情, 积极开展皮肤护理、高热护理、心理护理、饮食护理; 产后加强并发症预防和新生儿护理, 完善出院指导和居家随访。充分做好妊娠晚期合并水痘孕妇的临床护理工作, 可以有效减少母婴并发症的发生, 是确保母婴安全的重要有效措施。)